Household Livelihood Strategy of Patchouli Farmers in Sangia Tiworo Village, South Tiworo Sub-district, West Muna Regency - Safitrah, Safitrah; Marsuki Iswandi; Sitti Aida Adha Taridala (International Journal of Technology and Education Research, 2025)
Patchouli is a crop cultivated by most farmers in Sangia Tiworo Village. In addition to farming, they engage in other jobs to stabilize their household income. This strategy helps farmers meet their daily needs despite price fluctuations or the risk of crop failure in patchouli farming. This study aims to determine the household income of patchouli farmers and analyze their livelihood strategies in Sangia Tiworo Village, South Tiworo District, West Muna Regency. The data analysis methods used in this research are income analysis and qualitative descriptive analysis. This study presents two main findings. First, the average income of patchouli farmers is IDR 8,069,241 per harvest (excluding the first harvest) or approximately IDR 2,017,310.25 per month. Second, patchouli farmers in Sangia Tiworo Village implement three main livelihood strategies. They engage in agricultural livelihood adaptation by opening new farmland. They also adopt a diversified livelihood pattern, which includes on-farm income (patchouli cultivation), off-farm income (producing palm sugar, livestock farming, and providing wood-cutting services), and non-farm income (selling basic groceries and snacks). Lastly, they apply spatial livelihood adaptation by migrating outside the village to sell the palm sugar they produce